2012
DOI: 10.1037/a0029913
|View full text |Cite
|
Sign up to set email alerts
|

When role reversal and brokering meet: Filial responsibility among young immigrants to Israel from the former Soviet Union.

Abstract: Traditional conceptualizations of role reversal and brokering (language and cultural in immigration), in which children assume culturally atypical adult responsibilities, have developed as different scholarly domains, despite their theoretical similarity. The purpose of the present article is to increase the integration between the two bodies of literature to achieve a better understanding of filial responsibilities children assume upon immigration and their differential correlates with adjustment. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 57 publications
1
20
0
1
Order By: Relevance
“…Some participants perceive language mediation as a positive factor strengthening the self-esteem of the child, while others perceive it as a negative factor that increases their feeling of helplessness and dependence on children. Language brokering has been considered a stressor and a burden for an immigrant child, but at the same time as a factor having a variety of cognitive, emotional, and social benefits (Ponizovsky et al, 2012). Some studies describe the advantage of language mediation in terms of high academic achievement (Acoach & Web, 2004), selfconfidence (Buriel, Perez, de Ment, Chavez, & Moran, 1998), cooperation with family members, and closeness to parents (Dorner, Orellana & Jiménez, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some participants perceive language mediation as a positive factor strengthening the self-esteem of the child, while others perceive it as a negative factor that increases their feeling of helplessness and dependence on children. Language brokering has been considered a stressor and a burden for an immigrant child, but at the same time as a factor having a variety of cognitive, emotional, and social benefits (Ponizovsky et al, 2012). Some studies describe the advantage of language mediation in terms of high academic achievement (Acoach & Web, 2004), selfconfidence (Buriel, Perez, de Ment, Chavez, & Moran, 1998), cooperation with family members, and closeness to parents (Dorner, Orellana & Jiménez, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The greater adaptability of children and adolescents allows them to adjust to a new social environment, embrace new norms and values, and acquire the host language faster than their parents. As a result their role repertoire in the immigrant family is likely to expand (Mirsky & Prawer, 2003;Ponizovsky, Kurman, & Roer-Strier, 2012). At the same time, the feelings of loss and bereavement that often accompany immigrant parents' adjustment may impair their ability to meet their children's needs and lead to parent-child role confusion (Mann, 2004).…”
Section: Parenting and Parent-child Relationships In Immigrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Çocuklar okul ve sosyal aktiviteler nedeniyle yeni kültüre daha hızlı uyum sağladıklarından, ailelerinde dil aracılığı (language brokering) ve kültür aracılığı (culture brokering) gibi roller üstlenebilirler. Kültür aracılığı, ebeveynin yeni kültüre uyumuna yardımcı olmayı içerirken, dil aracılığı çevirmenlik rolünü ifade etmektedir (Ponizovsky, Kurman ve Roer-Strier, 2012). Duygusal ebeveynleşme, ebeveynlerin yeni kültüre uyum sağlamakta zorlanmaları durumunda daha fazla ortaya çıkmaktadır (Titzmann, 2012).…”
Section: Risk Faktörleri: Ebeveynleşmenin Sık Görüldüğü Aile öRüntüleriunclassified
“…Nevertheless, in accordance with the perspectives on children's resilience, adopting parental roles is not always seen as problematic. Empirical studies have shown that immigrant children who assume filial responsibilities develop high levels of empathy and responsibility, and an increased sense of self‐worth and respect (Hinton, ; Ponizovsky, Kurman, & Roer‐Strier, ). Positive contributions to intergenerational relations have also been reported and include better relations with parents and closer ties within families (Dorner, Orellana, & Jiménez, ).…”
Section: Literature Reviewmentioning
confidence: 99%